2019
DOI: 10.30838/j.pmhtm.2413.250619.13.316
|View full text |Cite
|
Sign up to set email alerts
|

Nanomodification of structure of non-ferrous metals in mode of superdeep penetration

Abstract: Анотація. Мета дослідження − встановити механізм надглибокого проникання речовин та залежності між параметрами мікрочастинок мікронних розмірів і глибиною надглибокого проникнення в армовані волокна. Методика. Як зразки для досліджень матричного матеріалу використовували мідь, латунь, алюмінієвий сплав АК12 і піддавали його динамічній обробці в режимі надглибокого проникнення. Шліфи до і після обробки досліджували за допомогою електронної мікроскопії, мікроаналізу, рентгеноструктурного та фазового аналізу, мас… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…An effective physical "tool" that changes mechanical [2], physical [3], chemical [4] and other metal properties [5] is the process of ultra-deep penetration of microparticles into metals (UPMM). Experience shows the superiority in the technological processes of products made of composite material, for example, cutters for the destruction of rocks [6], rubber-based composites withnano-sized fillers [7], polymer tracking membranes [8], non-ferrous metal composites [9] and the like other The effect is that microparticles of certain sizes and velocities areable to penetrate metallic materials to depths exceeding the size of microparticles up to several thousand of their caliber. New intermetallic phases formed in the metal matrix significantly affect its properties and significantly increase strength [10], corrosion resistance [11] and other important characteristics of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…An effective physical "tool" that changes mechanical [2], physical [3], chemical [4] and other metal properties [5] is the process of ultra-deep penetration of microparticles into metals (UPMM). Experience shows the superiority in the technological processes of products made of composite material, for example, cutters for the destruction of rocks [6], rubber-based composites withnano-sized fillers [7], polymer tracking membranes [8], non-ferrous metal composites [9] and the like other The effect is that microparticles of certain sizes and velocities areable to penetrate metallic materials to depths exceeding the size of microparticles up to several thousand of their caliber. New intermetallic phases formed in the metal matrix significantly affect its properties and significantly increase strength [10], corrosion resistance [11] and other important characteristics of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The recent experiments showed that when streams of cosmic dust particles collide with a spacecraft shield, it causes an occurrence of plasma, which in turn leads to the appearance of electromagnetic radiation capable of disabling nearby electrical equipment and superficial mechanical damage [1,6,7]. However, studies of dynamic alloying in the superdeep penetration (SDP) mode [2][3][4][5] also show that the collision of a high-speed cosmic dust streams should lead not only to electromagnetic radiation and superficial mechanical damage but also to penetration of cosmic dust particles into the spacecraft shell. Using dynamic alloying with high-speed streams of powder particles [10] will allow us to evaluate the effects that occur in the structure of material of the spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of powder compositions under dynamic loading provides dynamic alloying of the matrix material with the necessary materials. Currently, there are no generalized results of the process of the structure and properties changing under conditions of dynamic loading by a stream of high-speed particles depending on the initial materials; therefore, the choice of aluminum and its alloy is a development of work in this area of research [2,3,5].…”
Section: Introductionmentioning
confidence: 99%